"Valoracion morfoestructural y faneroptica de las gallinas criollas (Gallus domesticus) del Canton el Empalme, Provincia del Guayas". - España Vera, Erwin Daniel (2018)
The hen's backyard (470 adult animals) was characterized from 94 production units of the parishes of El Rosario, Velasco Ibarra and the Guayas, belonging to the canton "The joint", province of Guayas. The objective of the study was: a study of valuation morphostructural and faneroptica of native hens. 7 qualitative and 19 quantitative variables were evaluated. The descriptive analysis by sex showed greater weight in the roosters with 3.20 ±0, 03 and lower in hens, with 2.53 ± 0.02 kg/bird. It was observed high variability in the variables of the region of the head with the exception of peak, width, and length of head length; the region of the trunk and lower extremities variation was moderate, with the exception of the length of RAM which is normal in the male and stunted in females. The comparison between the sexes of the variable zoometric differences in males and females for the variables of the regions of the head, trunk, and extremities, that differentiate the population of males like animals heavy in relation to the females as example of sexual dimorphism. The characteristics faneropticas demonstrate dominance of dark colors (red, black, black) with red and marbled with 62,14; 67,14 and 94,17%, in the towns of the Guayas, El Rosario and Velasco Ibarra respectively. In the distribution of the plumage stands out the normal parish Velasco Ibarra (45.0%) and the naked neck with 77,14% in El Rosario; 55.0% in the Guayas and 48.3% in Velasco Ibarra. Abundant Crest type is the simplest in the three localities (95-100%), frequent Crest staining was the Red % 46,17 and red-hot 34,68%. Of the total sample dominant skin color was yellow (90,21%). Is concluded that the joint there is a wide diversity of kinds of hens Creole in canton and found in the backyard of rural farmers, the gene pool of these birds is an important tool for future conservation programs and genetic improvement to form production lines with hardiness and adaptation.